A Lifting Wavelet Domain Audio Watermarking Algorithm Based on the Statistical Characteristics of Sub-Band Coefficients - TAO, Zhi; ZHAO, He-ming; WU, Jun; GU, Ji-hua; XU, Yi-shen; WU, Di (Archives of Acoustics, 2010)
In this paper, a new lifting wavelet domain audio watermarking algorithm based on the statistical characteristics of sub-band coefficients is proposed. First of all, an original audio signal was segmented and each segment was divided into two sections. Then, the Barker code was used for synchronization, the LWT (lifting wavelet transform) was performed on each section, a synchronization code and a watermark were embedded into the first section and the second section, respectively, by modifying the statistical average value of the sub-band coefficients. The embed strength was determined adaptively according to the auditory masking property. Experiments show that the embedded watermark has better robustness against common signal processing attacks than present algorithms based on LWT and can resist random cropping in particular.